Pengaruh Metode Penilaian Persediaan dan Gross Profit Margin Terhadap Nilai Pasar (Studi Pada Perusahaan Dagang Yang Terdaftar Di Daftar Efek Syariah Periode 2009-2014) - Kinan Bahuweda Maulana; Ari Prasetyo (Universitas Airlangga, 2015)
This research attempt to know the influence of inventory valuation methods and gross profit margin againts market value of trading company that listed on Daftar Efek Syariah from 2009 through 2014. The independent variable was inventory valuation methods and gross profit margin, the dependent variable was market value. The analysis techniques used is multiple linear regression with variable dummy and the equation is FIFO method Ymv = 10,694 - 0,385 (0) + 0,127 (GPM)= 10,694 + 0,127 (GPM) and Average method Ymv = 10,694 - 0,385 (1) + 0,127 (GPM) = 10,309 + 0,127 (GPM).Based on the results of t-test, the inventory valuation methods has not a significant influence. Similarly, the gross profit margin partially has not significant influence to market value. The result of simultaneous test showed that inventory valuation methods, gross profit margin has significant effect to against market value of trading company.